تقييم الوضعية التنافسية للمؤسسات الصغيرة و المتوسطة في الجزائر -دراسة حالة مؤسسات قطاع النسيج بولاية تلمسان- - كلثوم, د.بوهنة; نصيرة, د.أوبختي (Recherches économiques et managériales; Vol. 18 (2015): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (Décembre), 2015)
ملخص    لقد أصبح موضوع تنمية المشروعات الصغيرة والمتوسطة في مختلف مجالات النشاط الاقتصادي من الموضوعات التي تلقى اهتماما متزايدا من طرف المنظمات الدولية والمحلية فضلا عن اهتمام الباحثين الاقتصاديين بها، باعتبارها أفضل الوسائل للإنعاش الاقتصادي نظرا لسهولة تكيفها ومرونتها التي تجعلها قادرة على الجمع بين التنمية الاقتصادية و الاجتماعية ووسيلة إيجابية لفتح آفاق العمل من خلال توفير مناصب الشغل وخلق الثروة، وبإمكانها رفع تحديات المنافسة وغزو الأسواق الخارجية في ظل اقتصاد السوق.    و من هذا المنطلق، فإن هذا الورقة البحثية البحث يهدف إلى تقييم الوضعية التنافسية للمؤسسات الصغيرة والمتوسطة في الجزائر، مع التركيز على دراسة بعض المؤسسات الصغيرة والمتوسطة لقطاع النسيج بولاية تلمسان، ضرورة الربط في الأفكار و الذي أصبح من القطاعات التي تعاني مشاكل كثيرة خاصة في ظل انفتاح الأسواق، وبالتالي لابد من دراسة تنافسية هذه المؤسسات أو إجاد الحلول لتنافسيتها الكلمات المفتاحية : المؤسسات الصغيرة و المتوسطة -التنافسية-التأهيل-قطاع النسيج. Abstract:     The subject of development of small and medium enterprises in various economic filed activities has become more and more important for international and local organisations, besides economic researchers since it is considered the best means to economic recovery because of its easy adaptation and flexibility which enable it to combine between economic development and social one as a positive medium for opening work horizons through providing jobs and making wealth as its possibility to increase the challenges of competition and invasion of foreign markets in market economy. With this in mind this research paper aims at assessing the competitive situation of small and medium sized enterprises in Algeria, focusing on the study of some small sized enterprises of the textile industry in the department of Tlemcen, and which has become among the sectors that suffer from a lot of problems particularly in light of the opening of markets, and thus we must find solutions to reduce these problems. Keywords: small and medium enterprises, competitiveness, qualifying, textile industry.